Faktor Demografi, Faktor Penyakit, dan Faktor Psikologis terhadap Makna Spiritual Pengalaman Sakit pada ODHA - Nurhayati Nurhayati; Rohman Azzam; Mustikasari Mustikasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to identify the relationship between demographic factors (age, gender, latest education, occupation, religion, economic status, marital status), disease factors (initial diagnosis, opportunistic infections, medication adherence), and psychological factors (anxiety and depression). the spiritual meaning of the experience of illness in people with HIV / AIDS (PLWHA) in East Jakarta. This research method uses a descriptive-analytic method with a cross-sectional study approach. The results of this study in the bivariate analysis obtained a p-value of 0.043, meaning that there is a relationship between age and the spiritual meaning of the experience of pain, in the multivariate analysis, opportunistic infections are the dominant factor associated with the spiritual meaning of pain experiences. In conclusion, opportunistic infections are the dominant factor related to the spiritual meaning of the experience of pain. Keywords: Demography, Spiritual Meaning, PLWHA, Illness, Psychology